Infografis Sebagai Media Pembelajaran Nilai Karakter Berbasis Project Base: Pendekatan Untuk Siswa Sekolah Dasar Di Geopark Bayah Dome: Infographics as a learning media for character values based on project base: Approach for Elementary School Students in Bayah Dome Geopark - Firdaus, Aryanty Putri; Haryani, Puput; Hanif, Muhammad; Khosihan, Aan; Setiawan, Budi (Efektor, 2023)
Infographic book media is a medium appropriate to the concrete thinking stages of elementary school students, which excitingly displays information visualization. This study intends to develop an infographic book introducing Geopark and instilling the Seven Enchantments character values for elementary school students, which is implemented in the local content curriculum in several elementary schools in the Bayah Dome Geopark area. Through research and development (R&D) methods with three main stages: (1) preliminary study stage, (2) design and development stage, 3) product testing stage. This research produces an infographic book product as an effort to recognize the potential of geoparks and character values that are used as supplementary media for local elementary school content. The results of this study are expected to be an alternative introduction to the potential of Geopark as a medium of learning and instilling character values targeting elementary school-age students. The development of Seven Enchantments-based infographic teaching materials in the Bayah Dome Geopark area is well implemented. Many students in the Bayah Dome Geopark area of Lebak Regency are interested in teaching materials with pictures contained in infographics. Reading visuals through pictures makes this fun teaching material book by Bayah more attractive and liked by students in elementary school. There is high enthusiasm for this infographic teaching material because it is easy for the teaching staff to understand. The use of this book has a positive impact on the application of Seven Enchantments-based character values in schools.